Pengembangan Pembelajaran Ekonomi Berkarakter Kebangsaan Melalui Model Trust Based Cooperative Learning Di SMA Negeri 5 Malang - Arbi Batulante (Jurnal Riset Kajian Teknologi dan Lingkungan, 2019)
Result of pre observation showed that economics learning in senior high school is tend to conventional learning or in general uses expository method so the students are only passive and are hoped can to understand and remember information that have explained by the teacher and able to retrieve what they have been understood by response that be showed when teacher is asking them. Above learning condition means that the economics learning process which is implemented for nowadays in the classroom is tend to teach competition culture which is more focus to liberalism values and forget for teaching high values of the nation contained in Pancasila and the 1945 constitution especially in article 33 namely togetherness culture, mutual aid (gotong royong), and kinship in learning. Referred to that case, so it is needed a research and economic learning development, nationality characterized by Trust Based Cooperative Learning Model to make economics learning that based to trust degree that is owned by students in cooperative learning and able to internalize the values contained in Pancasila and article 33 of 1945 constitution which refer to economic learning purpose contained in content standard. This study used model approach of Design Based Research in developing economic learning nationality characterized by Trust Based-cooperative learning model. The data analysis technique used was quantitative with statistic descriptive technique and qualitative. Based on the result of the study and development showed that the response of the students in experiment process in senior high school number 5 of Malang was 94%. it means that model scenario of Trust Based Cooperative Learning could make the students understand about economic concept which is relevant to Indonesian nation ideology especially able to build nationality character values for examples appreciate the togetherness, respect to others opinion, and deliberation for consensus.